Los contrastes y marcadores de la platería leonesa en los siglos XVII y XVIII - Herráez Ortega, María Victoria (Estudios humanísticos. Geografía, historia y arte, 1999)
This piece of research aims at finding out silver hallmarking worked in León in the 17th and 18th centuries. The City Council used to appoint a silversmith to hold the office of "Contraste y Marcador" every year, but usually the same person was appointed again and again until he died. The knowlege of the silvermarks this craftsman left is a source of information indispensable to catalogue the silver articles that came out of the leonese workshops.